2008
DOI: 10.4278/ajhp.22.6.417
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Tailored Feedback and Action Plans in an Intervention Addressing Multiple Health Behaviors

Abstract: Tailored lifestyle information can be effective for adults in changing nutrition behavior and physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
222
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(229 citation statements)
references
References 21 publications
3
222
1
2
Order By: Relevance
“…A recent meta-analysis shows tailoring is effective in changing health behavior, although the effect size appears to be relatively small (Noar, Benac, & Harris, 2007). Specific to weight management, tailoring has been found to improve both diet (de Vries, Kremers, Smeets, Brug, & Eijmael, 2008;Vandelanotte, De Bourdeaudhuij, Sallis, Spittaels, & Brug, 2005) and exercise (Bock, Marcus, Pinto, & Forsyth, 2001;. Tailoring research primarily focuses on mass communication, print, or computer-mediated materials.…”
Section: Differences In Effective Levels Of Acceptance and Challenge mentioning
confidence: 96%
“…A recent meta-analysis shows tailoring is effective in changing health behavior, although the effect size appears to be relatively small (Noar, Benac, & Harris, 2007). Specific to weight management, tailoring has been found to improve both diet (de Vries, Kremers, Smeets, Brug, & Eijmael, 2008;Vandelanotte, De Bourdeaudhuij, Sallis, Spittaels, & Brug, 2005) and exercise (Bock, Marcus, Pinto, & Forsyth, 2001;. Tailoring research primarily focuses on mass communication, print, or computer-mediated materials.…”
Section: Differences In Effective Levels Of Acceptance and Challenge mentioning
confidence: 96%
“…A metaanalytical review of 24 randomized controlled trials of interactive health communication for people with chronic diseases showed that they were more effective than standard interventions for improving people's knowledge, self-efficacy, social support, and improvements in exercise, and reductions in smoking [58]. de Vries et al [59] found that computer-tailored printed letters were more effective than standard letters in improving Dutch participants' nutrition and physical activity, but smoking cessation rates were similar for both groups. A review of 14 interventions using mobile telephone short-message text service (SMS) to educate users about smoking cessation and diabetes self-management found that the features of interactivity and information tailoring were associated with short-term behavioral improvements.…”
Section: Evidence From Ehealth Research On Interventions?mentioning
confidence: 97%
“…A meta-analytical review of 24 randomized controlled trials of interactive health communication for people with chronic diseases showed that they were more effective than standard interventions to improve people's knowledge, selfefficacy, social support, and improvements in continuous (''step-wise'' results, such as increasing exercise), but not binary (''yes or no'' results, such as smoking or not smoking) behavioral outcomes (Murray et al 2005). de Vries et al (2008) found that computer-tailored printed letters were more effective than standard letters in improving Dutch participants' nutrition and physical activity, but smoking cessation rates were similar for both groups. A review of 14 interventions using the mobile telephone short-message text service to educate users about smoking cessation and diabetes self-management found that the features of interactivity and information tailoring were associated with short-term behavioral improvements.…”
Section: Effects On Other Health Behaviorsmentioning
confidence: 99%